The lived career experiences of Black and Minoritised Ethnic female academic leaders in higher education at the intersections of race, gender, ethnicity and social class - Barnes, Charmagne (2022)
This qualitative study explores the experiences of eight Black and Minoritised Ethnic (BME) women in academic leadership in higher education (HE). Using intersectionality as key and theoretical perspectives that keep race at the centre, this study explores their lived career experiences in HE leadership at the intersections of their multiple identities of race, gender, ethnicity, and social class. Using an intersectional feminist methodology of narrative inquiry and the life history method, the BME women participated by completing an adapted career grid and two semi-structured interviews. Through these, they told stories of their lived career experiences that identified challenges and sources of personal and professional support to help them overcome and navigate their leadership journey. The findings of the study show that structural inequalities cause workplace racial inequality, discrimination, and marginalisation for BME women because of their intersecting multiple identities. Institutional racism encompassing white privilege renders them invisible as leaders and discriminatory racial microaggressions cause distress. Despite the challenges encountered, BME women want to engage with academic leadership and draw on their personal identity, social, ethnic and cultural capitals to enact their leadership practice. Furthermore, they add to their professional, resistant and navigational capitals through the acquisition of professional and institutional resources and sources of support. Acculturation, bicultural competence, white sanction, and the accumulation of social capital were strategies adopted to enable them to fit into the organisation and navigate institutional racism and intersectionality between races. Their leadership practice has a critical race perspective which is influenced by their personal values and their lived experiences. It is ethical, relational, and has a focus on social justice. Implications for institutional policy, practice, and research in educational: leadership, management, human resources, and research are discussed and suggested.